Peer-delivered services for substance use in low- and middle-income countries: A systematic review - Satinsky, E.N.; Kleinman, M.B.; Tralka, H.M.; Jack, H.E.; Myers-Franchi, Bronwyn; Magidson, J.F. (2021)
Background and aims: Addressing the burden of disease associated with substance use is a global priority, yet access to treatment is limited, particularly in low- and middle-income countries (LMICs). Peers, individuals with lived experience of substance use, may play an important role in expanding access to treatment, supporting outcomes, and reducing stigma. While peer-delivered services for substance use have been scaling up in high-income countries (HICs), less is known about their application in LMICs. This systematic review synthesizes the evidence of peer-delivered services for substance use in LMICs. Methods: PsycINFO, Embase, Global Health, PubMed, and six region-specific databases were searched, and articles that described peer-delivered services for substance use and related outcomes in LMICs were included. Risk of bias was evaluated using tools appropriate for each study design. To provide a more stringent evaluation of structured interventions, a subset of articles was analyzed using the Cochrane Effective Practice and Organization of Care (EPOC) framework. Results: The search yielded 6540 articles. These were narrowed down to 34 included articles. Articles spanned four continents, included quantitative and qualitative methodologies, and primarily targeted infectious disease risk behaviors. Ten articles were included in the EPOC sub-analysis. In the context of high risk of bias, some of these articles demonstrated positive impacts of the peer-delivered services, including reductions in risk behaviors and increases in infectious disease knowledge scores, while many others showed no significant difference in outcomes between peer intervention and control groups. Conclusions: Peer-delivered services may be feasible for addressing substance use and reducing infectious disease risk behaviors in LMICs, where there are severe human resource shortages. Globally, peers’ lived experience is valuable for engaging patients in substance use treatment and harm reduction services. Further research is needed to better characterize and quantify outcomes for peer-delivered services for substance use in LMICs.